Measurement of Non-academic Attributes in the Situational Judgment Test as Part of School Teacher Selection: Systematic Literature Review - Nadmilail, Azad Iqram; Matore, Mohd Effendi @ Ewan Mohd; Maat, Siti Mistima (International Journal of Learning, Teaching and Educational Research, 2022)
The Situational Judgment Test (SJT) has become an increasingly well-known measurement method that is frequently used in various fields, especially for personnel selection, promotion, and professional development. The SJT also has a greater potential in relation to the selection of teachers in the education sector. Teacher selection aspects such as non-academic attributes, specifically the interpersonal and intrapersonal, are the focus of this study. This study uses a Systematic Literature Review (SLR) consisting of a review protocol to determine the topic that has been researched and the method used for making revisions. The SLR approach has four phases: searching, screening, analysing, and the results with numerous criteria established. The review consists of seven studies on teacher selection using the SJT instrument over the past ten years during the period January 2012 to December 2021. Eight interpersonal attributes were obtained based on six previous studies, namely organisation, planning, empathy, communication, teaching, relationships with colleagues, counselling, and contingency. Meanwhile seven intrapersonal attributes were obtained, namely conscientiousness, mindset, emotion regulation, adaptability, enthusiasm and motivation, resilience, and professional ethics. The attributes found can be utilised as they are fundamental for teacher selection criteria. The previous studies employed the same attributes. However, the attributes should only be employed according to the suitability of the selection context being performed. https://doi.org/10.26803/ijlter.21.5.14